Method of producing cured product
Patent Information
- Application Number
- JP2024221246
- Authority / Receiving Office
- JP · JP
- Patent Type
- Applications
- Current Assignee / Owner
- Filing Date
- 2024-12-18
- Publication Date
- 2025-02-28
AI Technical Summary
【0017】 本発明のオルガノポリシロキサンは、1分子中に特定の構成単位としてアルコキシ-メチレン-ケイ素結合を有し、ジメチルシロキシ単位(D単位)がシルエチレン構造を介してポリマーにポリジメチルシロキシ構造として導入されており、かつアルコキシシリル基および/またはシラノール基を有しているため、従来のシリコーンレジンやシリコーンアルコキシオリゴマーに比べて可とう性に優れ、また、疎水性、水滑落性等の表面防汚特性にも優れている。 さらに、本発明のオルガノポリシロキサンは、有機スズ化合物の代わりにアミン系化合物を硬化触媒として用いた場合でも速硬化性に優れ、硬度と耐屈曲性とを両立し得る硬化物を与えるという特性も有している。 このような特性を有する本発明のオルガノポリシロキサンを含む組成物は、コーティング剤等の材料を形成する硬化性組成物として好適に用いることができる。
Smart Images

Figure 2025028263000001 
Figure 2025028263000002 
Figure 2025028263000003
Abstract
Description
[Technical field]
[0001] The present invention relates to a method for producing a cured product. [Background technology]
[0002] Silicone resins are currently widely used in a variety of fields due to their excellent properties, such as water repellency, heat resistance, weather resistance, cold resistance, electrical insulation, chemical resistance, and safety to the human body. In particular, SiO 4 / 2 Units (Q units) and RSiO 3 / 2 Organopolysiloxanes with a three-dimensional crosslinked structure whose main component is a unit (T unit) (R is an organic group such as an alkyl group or a phenyl group) are called silicone resins or silicone alkoxy oligomers, and taking advantage of their curing properties, they are widely used in paints, coatings, binders, and other applications.
[0003] In particular, liquid silicone alkoxy oligomers with alkoxysilyl groups as crosslinking groups are used as the base agent for solvent-free paints that do not contain flammable organic solvents that are harmful to the human body (Non-Patent Document 1). In addition, this alkoxysilyl group undergoes hydrolysis and dehydration condensation crosslinking reaction at room temperature due to the moisture in the air, so the silicone alkoxy oligomer containing alkoxysilyl group can form a siloxane network by reacting the alkoxysilyl group at room temperature by adding a curing catalyst.This type of polysiloxane cured film is excellent in heat resistance and weather resistance, so it is used in a wide range of fields, from outdoor buildings to electronic parts. Furthermore, as mentioned above, the curing reaction of silicone alkoxy oligomers proceeds even at room temperature, but the reaction can be accelerated by heating. Depending on the application, a heat curing process can be appropriately introduced, making this a technology with excellent coating adaptability.
[0004] However, while such silicone resins and silicone alkoxy oligomers have the advantages of good curing properties and high surface hardness due to their three-dimensional crosslinked structure, they also have issues such as a lack of flexibility and bending resistance due to their high crosslink density, which can lead to cracks in the coating film over time after formation or when external stress is applied. In order to improve this flexibility and bending resistance, diorganosiloxane (RSiO) is produced by using diorganoxyalkoxysilane in combination with silicone resin or silicone alkoxy oligomer during synthesis by hydrolysis condensation. 2 / 2 The most common method is to incorporate D units (D units). However, in this case, the D units are incorporated randomly into the structure, so in order to impart flexibility, it is necessary to add a large number of D units, which poses the problem of reducing the excellent curing properties and surface hardness that are the advantages of silicone resins.
[0005] In addition, a method of adding silicone oil whose molecular ends are blocked with TEOS (Si(OCH2CH3)4) has been proposed (Non-Patent Document 1), but this has poor compatibility with silicone resins and silicone alkoxy oligomers, causing the coating to become cloudy and to repel.
[0006] Another method for introducing D units into silicone alkoxy oligomers is to chemically bond a hydrosilyl group to an alkylolefin using a platinum catalyst or the like. This reaction is generally called a hydrosilylation reaction, and it is known that this reaction can be used to introduce an alkoxysilyl group into a linear silicone via a silethylene structure (Patent Documents 1 and 2).
[0007] Patent Document 1 discloses an organopolysiloxane that contains both a silicone alkoxy oligomer structure having an alkoxysilyl group in one molecule and a structure derived from a side chain methyl / phenyl type silicone oil structure, the organopolysiloxane being obtained by subjecting a side chain methyl / phenyl type silicone oil compound that contains hydrosilyl groups and is composed of a chain structure of D units to a hydrosilylation reaction with a silicone alkoxy oligomer compound that has both an olefin and an alkoxysilyl group in the side chain.
[0008] The organopolysiloxane of Patent Document 1 has a relatively long-chain, high-molecular-weight silicone oil structure with a methyl / phenyl side chain. Therefore, while it is effective when added as an agent for imparting crack resistance, when cured by itself it does not provide sufficient hardness, making it difficult to use by itself in paints and coatings.
[0009] Furthermore, the technology of Patent Document 2 focuses on improving the feel of linear silicone in hair treatment agents and the like, and does not mention its application as a flexible coating material.
[0010] In this way, in silicone alkoxy oligomers in which D units have been introduced by hydrosilylation, the D units are introduced locally compared to the random hydrolysis condensation method mentioned above, making it easier to express the properties of diorganopolysiloxane. However, there is still a decrease in the hydrolysis resistance of the alkoxysilyl moieties, and there is a demand for improvements in reactivity (moisture curing).
[0011] In addition, in order to ensure sufficient reactivity (moisture curing) at room temperature, it is generally necessary to add a catalyst such as an organometallic compound, and among these, the addition of an organotin compound is particularly effective. However, there are concerns about the toxicity of organotin compounds, which are usually used as catalysts, to the human body and the environment, and environmental regulations have become stricter in recent years, so their use has been avoided. Furthermore, when an organometallic catalyst such as an organotin compound is used in a dealcohol-removing type room-temperature curable composition, the siloxane bond in the main chain is cleaved (cracked) by the generated alcohol, which causes problems such as poor storage stability, such as a decrease in curability and an increase in viscosity over time. [Prior art documents] [Patent documents]
[0012] [Patent Document 1] Japanese Patent Application Publication No. 6-271650 [Patent Document 2] International Publication No. 2004 / 091562 [Non-patent literature]
[0013] [Non-Patent Document 1] Polymeric Materia1s Science and Engineering,1998,Vol.79,192 Summary of the Invention [Problem to be solved by the invention]
[0014] The present invention has been made in consideration of the above circumstances, and has an object to provide a method for producing a cured product that combines hardness and flex resistance, and further has excellent contamination removal properties such as hydrophobicity and the ability to allow water droplets to slide off. [Means for solving the problem]
[0015] The present inventors have conducted intensive research to solve the above-mentioned problems, and as a result have found that an organopolysiloxane having an alkoxy-methylene-silicon bond as a specific structural unit in one molecule, and also having an alkoxysilyl group and / or a silanol group, and further having D units introduced as block segments via silethylene bonds, is fast-curing even when an amine compound is used as a curing catalyst instead of an organotin compound, and gives a cured product that is able to satisfy high levels of hardness, flexibility, and hydrophobicity / water slippage, and that a composition containing this compound is suitable as a curable composition for forming a material for a coating agent or the like, thereby completing the present invention.
[0016] That is, the present invention provides 1. A method for producing a cured product, comprising curing a curable composition containing (A) an organopolysiloxane having a structural unit represented by the following general formula (1), a structural unit represented by the following general formula (2), and a group represented by the following general formula (3) directly bonded to a silicon atom, and (B) a curing catalyst: [ka] (In the formula, R 1 represents an unsubstituted or substituted alkyl group having 1 to 12 carbon atoms, or an unsubstituted or substituted aryl group having 6 to 10 carbon atoms. [ka] (In the formula, R 2 each independently represents an unsubstituted or substituted alkyl group having 1 to 12 carbon atoms, or an unsubstituted or substituted aryl group having 6 to 10 carbon atoms, each n independently represents 2 or 3, and m represents an integer of 5 to 100. [ka] (In the formula, R 3 represents a hydrogen atom, an unsubstituted or substituted alkyl group having 1 to 10 carbon atoms, or an unsubstituted or substituted aryl group having 6 to 10 carbon atoms. 2. A method for producing a cured product according to claim 1, comprising applying the curable composition to a surface of a solid substrate and curing the composition; 3. A method for producing a cured product according to 1 or 2, wherein the average structure of the organopolysiloxane is represented by the following formula (4): [ka] (In the formula, R 1 , R 2 , R 3 , n and m have the same meanings as above, R 4 , R 5 and R 6 each independently represents a monovalent organic group, and a, b, c, d, e, f, and g represent the numbers a>0, b>0, c≧0, d≧0, e≧0, f≧0, and g>0. 4. A method for producing a cured product according to claim 3, wherein the average structure of the organopolysiloxane is represented by the following formula (5): [ka] (In the formula, R 1 , R 2 , R 3 , R 4 , n, m, a, b, and g have the same meanings as above, and d represents a number d>0. 5. The method for producing a cured product according to any one of 1 to 4, wherein the curing catalyst (B) is an amine compound. to provide. Effect of the Invention
[0017] The organopolysiloxane of the present invention has an alkoxy-methylene-silicon bond as a specific structural unit in one molecule, dimethylsiloxy units (D units) are introduced into the polymer as a polydimethylsiloxy structure via a silethylene structure, and has alkoxysilyl groups and / or silanol groups, so that it has superior flexibility compared to conventional silicone resins and silicone alkoxy oligomers, and also has excellent surface anti-fouling properties such as hydrophobicity and water sliding properties. Furthermore, the organopolysiloxane of the present invention has the property of being fast curing even when an amine compound is used as the curing catalyst instead of an organotin compound, and of giving a cured product that is both hard and flexible. Compositions containing the organopolysiloxane of the present invention having such properties can be suitably used as curable compositions for forming materials for coating agents and the like. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0018] The present invention will be specifically described below. The organopolysiloxane according to the present invention has a structural unit represented by the following general formula (1), a structural unit represented by the following general formula (2), and a group represented by the following general formula (3) that is directly bonded to a silicon atom.
[0019] [ka]
[0020] Here, R 1 represents an unsubstituted or substituted alkyl group having 1 to 12 carbon atoms, preferably 1 to 3 carbon atoms, or an unsubstituted or substituted aryl group having 6 to 10 carbon atoms. R 1 The alkyl group having 1 to 12 carbon atoms may be linear, cyclic, or branched, but is preferably a linear or branched alkyl group, and more preferably a linear alkyl group. Specific examples thereof include methyl, ethyl, n-propyl, n-butyl, s-butyl, t-butyl, n-pentyl, n-hexyl, n-heptyl, n-octyl, n-nonyl, n-decyl, n-undecyl, and n-dodecyl groups, with methyl, ethyl, and t-butyl groups being preferred, methyl and ethyl groups being more preferred, and methyl groups being even more preferred. Specific examples of the aryl group having 6 to 10 carbon atoms include phenyl and naphthyl groups, with the phenyl group being preferred. In particular, from the viewpoint of hardening and hardness, R 1is preferably an alkyl group having 1 to 3 carbon atoms.
[0021] Above R 2 represents an unsubstituted or substituted alkyl group having 1 to 12 carbon atoms, preferably 1 to 3 carbon atoms, or an unsubstituted or substituted aryl group having 6 to 10 carbon atoms. R 2 The alkyl group having 1 to 12 carbon atoms may be linear, cyclic, or branched, but is preferably linear or cyclic, and more preferably linear. Specific examples thereof include methyl, ethyl, n-propyl, n-butyl, s-butyl, t-butyl, n-pentyl, n-cyclopentyl, n-hexyl, n-cyclohexyl, n-heptyl, n-octyl, n-nonyl, n-decyl, n-undecyl, and n-dodecyl groups, with methyl and ethyl groups being preferred, and methyl group being more preferred. Specific examples of the aryl group having 6 to 10 carbon atoms include phenyl and naphthyl groups, with the phenyl group being preferred. In particular, from the viewpoint of imparting flexibility, hydrophobicity and water sliding properties, R 2 is preferably an alkyl group having 1 to 3 carbon atoms.
[0022] The above n corresponds to a unit to be introduced into the siloxane resin or oligomer main structure, and can be 2 or 3, with 2 being preferred. The above m is the number of units in the dimethylpolysiloxane chain and can be 5 to 100, preferably 10 to 90, and more preferably 20 to 60. If m is more than 100, problems such as poor reactivity with the vinylsiloxane portion of the main chain in the hydrosilylation reaction described below can occur.
[0023] Above R 3 represents a hydrogen atom, an unsubstituted or substituted alkyl group having 1 to 10 carbon atoms, or an unsubstituted or substituted aryl group having 6 to 10 carbon atoms. R 3The alkyl group having 1 to 10 carbon atoms may be linear, cyclic, or branched, but is preferably a linear alkyl group. Specific examples thereof include methyl, ethyl, n-propyl, n-butyl, n-pentyl, n-hexyl, n-heptyl, n-octyl, n-nonyl, and n-decyl groups, with methyl, ethyl, n-propyl, n-hexyl, and n-octyl groups being preferred, methyl and ethyl groups being more preferred, and methyl being even more preferred. Specific examples of the aryl group having 6 to 10 carbon atoms include phenyl and naphthyl groups, with the phenyl group being preferred. In particular, from the viewpoint of hardening, R 3 is preferably a hydrogen atom or an alkyl group having 1 to 3 carbon atoms, and more preferably a hydrogen atom, a methyl group, or an ethyl group.
[0024] In addition, the above R 1 , R 2 and R 3 Some or all of the hydrogen atoms of the alkyl group or aryl group may be substituted with halogen atoms such as F, Cl, Br, etc., or other substituents such as a cyano group. Specific examples of such groups include halogen-substituted alkyl groups such as a 3,3,3-trifluoropropyl group; and cyano-substituted alkyl groups such as a 2-cyanoethyl group.
[0025] The organopolysiloxane of the present invention is not particularly limited as long as it has a structural unit represented by the above general formula (1), a structural unit represented by the above general formula (2), and a group represented by the above general formula (3) directly bonded to a silicon atom, and may have a linear structure, branched structure, or crosslinked structure consisting of an organopolysiloxane skeleton.
[0026] More specifically, the organopolysiloxane of the present invention is preferably one whose average structure is represented by the following formula (4). By using such an organopolysiloxane, even better fast curing properties, hardness, flex resistance, hydrophobicity, and water sliding properties are exhibited.
[0027] [ka] (In the formula, R 1 , R 2 , R 3 , n and m have the same meanings as above.)
[0028] Here, R 4 , R 5 and R 6 each independently represents a monovalent organic group. The monovalent organic group is not particularly limited, and examples thereof include R 1 Examples of the alkyl group include those having 1 to 12 carbon atoms and those having 6 to 10 carbon atoms. In addition, some or all of the hydrogen atoms of these alkyl and aryl groups may be substituted with a substituent. Examples of such substituents include halogen atoms, alkenyl groups such as a vinyl group, a glycidyl-type epoxy group, an alicyclic epoxy group, a thiirane group, a (meth)acryloyloxy group, a mercapto group, an iso(thio)cyanate group, a succinic anhydride group, an amino group, an ethylenediamino group, a perfluoroalkyl group, a polyether group such as a polyoxyethylene group, a perfluoropolyether group, and the like.
[0029] Also, R 4 , R 5 and R 6 may be two or more different monovalent organic groups, in which case the content ratio of the two or more different monovalent organic groups is arbitrary and is not particularly limited as long as the total value of the content ratio of the two or more different monovalent organic groups is 1. For example, R 4 For example, R is 0.5 alkyl and 0.5 aryl. 5 For example, the alkyl group is 0.2 and the glycidyl-type epoxy group-containing alkyl group is 0.8. In addition, the content ratio can be arbitrarily selected from the various monovalent organic groups described above, and any content ratio can be adopted.
[0030] Among these, R 4 , R 5 and R 6From the viewpoints of fast curing property, hardness and flex resistance, is preferably an unsubstituted alkyl group having 1 to 12 carbon atoms, an unsubstituted aryl group having 6 to 10 carbon atoms, a glycidyl type epoxy group, a (meth)acrylic group or a mercapto group, more preferably an unsubstituted alkyl group having 1 to 12 carbon atoms. From the viewpoint of supplyability of the raw material, a methyl group or a phenyl group is even more preferable.
[0031] a, b, c, d, e, f and g represent the numbers a>0, b>0, c≧0, d≧0, e≧0, f≧0, g>0, but from the viewpoints of fast curing, hardness, bending resistance, hydrophobicity and water sliding, the numbers 1000≧a>0, 1000≧b>0, 500≧c≧0, 1000≧d≧0, 1000≧e≧0, 100≧f≧0, 1000≧g>0 are preferred, the numbers 500≧a>0, 500≧b>0, 100≧c≧0, 500≧d≧0, 500≧e≧0, 50≧f≧0, 500≧g>0 are more preferred, and the numbers 500≧a>0, 500≧b>0, c=0, 500≧d>0, e=0, f=0, 500≧g>0 are even more preferred.
[0032] Therefore, the organopolysiloxane of the present invention is preferably one whose average structure is represented by the following formula (5). By using such an organopolysiloxane, even better fast curing properties, hardness, flex resistance, hydrophobicity, and water sliding properties are exhibited.
[0033] [ka] (In the formula, R 1 , R 2 , R 3 , R 4 , n, m, a, b, and g have the same meanings as above, and d represents a number d>0.)
[0034] The weight average molecular weight of the organopolysiloxane of the present invention is not particularly limited, but in consideration of imparting sufficient fast curing properties, hardness, bending resistance, hydrophobicity, and water sliding properties to the cured product obtained by curing a curable composition containing the compound, the weight average molecular weight is preferably 1,500 to 200,000, more preferably 5,000 to 100,000, and even more preferably 10,000 to 80,000. Note that the weight average molecular weight in the present invention is a polystyrene-equivalent value measured by gel permeation chromatography (GPC).
[0035] The organopolysiloxane of the present invention can be produced by copolymerizing a trialkoxysilane represented by the following structural formula (6) (hereinafter referred to as trialkoxysilane (6)), a vinylalkoxysilane represented by the following structural formula (7) (hereinafter referred to as vinylalkoxysilane (7)), and, as an optional component, various alkoxysilanes represented by the following structural formulas (9), (10), (11) and (12) (hereinafter referred to as alkoxysilanes (9), (10), (11) or (12) respectively) and / or partial hydrolysis condensates thereof, through hydrolysis and dehydration condensation to obtain the corresponding vinyl group-containing organopolysiloxane, and then subjecting this vinyl group-containing organopolysiloxane to a hydrosilylation reaction with an organohydrogenpolysiloxane represented by the following structural formula (8).
[0036] [ka] (In the formula, R 1 ~R 6 , n and m have the same meanings as above.)
[0037] Specific examples of trialkoxysilanes (6) include methoxymethyltrimethoxysilane, ethoxymethyltriethoxysilane, and the like. Taking into consideration the rapid curing properties, hardness, flexibility, hydrophobicity, and water sliding properties of the resulting organopolysiloxane, methoxymethyltrimethoxysilane and ethoxymethyltriethoxysilane are preferred.
[0038] Specific examples of trialkoxysilanes (7) include vinyltrimethoxysilane, vinyltriethoxysilane, vinylmethyldimethoxysilane, vinylmethyldiethoxysilane, vinylethyldimethoxysilane, vinylethyldiethoxysilane, vinylhexyldimethoxysilane, vinylhexyldiethoxysilane, vinyloctyldimethoxysilane, vinyloctyldiethoxysilane, vinylphenyldimethoxysilane, vinylphenyldiethoxysilane, and the like. In consideration of the fast curing properties, hardness, flexibility, hydrophobicity, and water sliding properties of the resulting organopolysiloxane, as well as marketability as a raw material, vinyltrimethoxysilane, vinyltriethoxysilane, and vinylmethyldimethoxysilane are preferred.
[0039] Specific examples of the optional alkoxysilane (9) include tetramethoxysilane, tetraethoxysilane, tetrapropoxysilane, tetraisopropoxysilane, tetrabutoxysilane, and tetraoctoxysilane.
[0040] Specific examples of the optional alkoxysilane (10) include methyltrimethoxysilane, propyltrimethoxysilane, hexyltrimethoxysilane, octyltrimethoxysilane, decyltrimethoxysilane, phenyltrimethoxysilane, naphthyltrimethoxysilane, allyltrimethoxysilane, hexenyltrimethoxysilane, octenyltrimethoxysilane, methyltriethoxysilane, propyltriethoxysilane, hexyltriethoxysilane, octyltriethoxysilane, decyltriethoxysilane, and phenyltriethoxysilane. silane, naphthyltriethoxysilane, allyltriethoxysilane, hexenyltriethoxysilane, octenyltriethoxysilane, 2-(3,4-epoxycyclohexyl)ethyltrimethoxysilane, 2-(3,4-epoxycyclohexyl)ethyltriethoxysilane, 3-glycidoxypropyltrimethoxysilane, 3-glycidoxypropyltriethoxysilane, 8-glycidoxyoctyltrimethoxysilane, 8-glycidoxyoctyltriethoxysilane, p-styryltrimethoxysilane, p-styryltriethoxysilane, meth Acryloxymethyltrimethoxysilane, methacryloxymethyltriethoxysilane, 3-methacryloxypropyltrimethoxysilane, 3-methacryloxypropyltriethoxysilane, 8-methacryloxyoctyltrimethoxysilane, 8-methacryloxyoctyltriethoxysilane, acryloxymethyltrimethoxysilane, acryloxymethyltriethoxysilane, 3-acryloxypropyltrimethoxysilane, 3-acryloxypropyltriethoxysilane, 8-acryloxyoctyltrimethoxysilane, 8-acryloxyoctyl Triethoxysilane, N-2-(aminoethyl)-aminomethyltrimethoxysilane, N-2-(aminoethyl)-aminomethyltriethoxysilane, N-2-(aminoethyl)-3-aminopropyltrimethoxysilane, N-2-(aminoethyl)-3-aminopropyltriethoxysilane, N-2-(aminoethyl)-8-aminooctyltrimethoxysilane, N-2-(aminoethyl)-8-aminooctyltriethoxysilane, aminomethyltrimethoxysilane, aminomethyltriethoxysilane, 3-aminopropyltrimethoxysilane,3-Aminopropyltriethoxysilane, 8-aminooctyltrimethoxysilane, 8-aminooctyltriethoxysilane, N-phenyl-aminomethyltrimethoxysilane, N-phenyl-aminoethyltrimethoxysilane, N-phenyl-3-aminopropyltrimethoxysilane, N-phenyl-3-aminopropyltriethoxysilane, N-phenyl-8-aminooctyltrimethoxysilane, N-phenyl-8-aminooctyltriethoxysilane, 3-isocyanatepropyltrimethoxysilane, 3-isocyanatepropyltriethoxysilane, mercaptomethyltrimethoxysilane, mercaptomethyltriethoxysilane, 3-mercaptopropyltrimethoxysilane, 3-mercaptopropyltriethoxysilane, 8-mercaptooctyltrimethoxysilane, 8-mercaptooctyltriethoxy Silane, 3-trimethoxysilylpropyl succinic anhydride, 3-triethoxysilylpropyl succinic anhydride, chloromethyl trimethoxysilane, chloromethyl triethoxysilane, 3-chloropropyl trimethoxysilane, 3-chloropropyl triethoxysilane, 8-chlorooctyl trimethoxysilane, 8-chlorooctyl triethoxysilane, trifluoropropyl trimethoxysilane, nonafluorohexyl trimethoxysilane, tridecafluorooctyl trimethoxysilane, polyethylene glycol methyl-3-trimethoxysilylpropyl ether, polyethylene glycol methyl-3-triethoxysilylpropyl ether, polypropylene glycol methyl-3-trimethoxysilylpropyl ether, polypropylene glycol methyl-3-triethoxysilylpropyl ether, etc.,
[0041] Among these, the alkoxysilane (10) is preferably methyltrimethoxysilane, methyltriethoxysilane, phenyltrimethoxysilane, 3-glycidoxypropyltrimethoxysilane, 3-glycidoxypropyltriethoxysilane, 3-methacryloxypropyltrimethoxysilane, 3-acryloxypropyltrimethoxysilane, 3-mercaptopropyltrimethoxysilane, 3-mercaptopropyltriethoxysilane, nonafluorohexyltrimethoxysilane, tridecafluorooctyltrimethoxysilane, or polyethylene glycol methyl-3-trimethoxysilylpropyl ether, and more preferably methyltrimethoxysilane or methyltriethoxysilane.
[0042] Specific examples of the optional alkoxysilane (11) include dimethyldimethoxysilane, dimethyldiethoxysilane, methylphenyldimethoxysilane, methylphenyldiethoxysilane, diphenyldimethoxysilane, diphenyldiethoxysilane, octenylmethyldimethoxysilane, 2-(3,4-epoxycyclohexyl)ethylmethyldimethoxysilane, 3-glycidoxypropylmethyldimethoxysilane, 3-glycidoxypropylmethyldiethoxysilane, 3-methacryloxypropylmethyldimethoxy ... Examples of the silane include dipropylmethyldiethoxysilane, 3-acryloxypropylmethyldimethoxysilane, N-2-(aminoethyl)-3-aminopropylmethyldimethoxysilane, N-2-(aminoethyl)-3-aminopropylmethyldiethoxysilane, 3-aminopropylmethyldimethoxysilane, 3-aminopropylmethyldiethoxysilane, 3-mercaptopropylmethyldimethoxysilane, 3-mercaptopropylmethyldiethoxysilane, 3-chloropropylmethyldimethoxysilane, and 3-chloropropylmethyldiethoxysilane.
[0043] Among these, as the alkoxysilane (11), dimethyldimethoxysilane, dimethyldiethoxysilane, diphenyldimethoxysilane, 3-glycidoxypropylmethyldimethoxysilane, and 3-glycidoxypropylmethyldiethoxysilane are preferred, and dimethyldimethoxysilane and dimethyldiethoxysilane are more preferred.
[0044] Specific examples of the optional alkoxysilane (12) include trimethylmethoxysilane, trimethylethoxysilane, vinyldimethylmethoxysilane, 3-methacryloxypropyldimethylmethoxysilane, 3-methacryloxypropyldimethylethoxysilane, 3-acryloxypropyldimethylmethoxysilane, 3-acryloxypropyldimethylethoxysilane, N-2-(aminoethyl)-3-aminopropyldimethylmethoxysilane, and N-2-(aminoethyl)-3-aminopropyldimethylethoxysilane, with trimethylmethoxysilane being preferred.
[0045] Specific examples of organohydrogenpolysiloxanes (8) include those in which the number m of dimethylsiloxy units is, on average, 8, 20, 40, 60, and 90. Of these, those in which m is 20 or 40 are preferred from the viewpoints of hydrosilylation reactivity, hydrophobicity exhibited, water sliding properties, and imparting flexibility to the coating.
[0046] The copolymerization by hydrolysis and dehydration condensation of trialkoxysilanes (6) and (7) with optional alkoxysilanes (9) to (12) is usually carried out without a solvent, but may be carried out in the presence of an organic solvent that dissolves all of the alkoxysilanes used in the reaction (e.g., methanol, ethanol, isopropyl alcohol, butanol, diacetone alcohol, propylene glycol monomethyl ether, propylene glycol monomethyl ether acetate, acetone, toluene, xylene, etc.). When an organic solvent is used, its amount is not particularly limited, but is usually preferably 20 parts by mass or less, more preferably 0.1 to 10 parts by mass, and even more preferably 0.5 to 5 parts by mass, per part by mass of the total mass of the trialkoxysilanes (6) and (7) and the optional alkoxysilanes (9) to (12).
[0047] The copolymerization by hydrolysis and dehydration condensation is carried out by dropping or pouring an acid or base that serves as a catalyst for the hydrolysis reaction and water into the above-mentioned mixture or solution of alkoxysilane. In this case, the acid or base may be dropped in the form of an aqueous solution. The acid is not particularly limited, and examples thereof include hydrochloric acid, sulfuric acid, nitric acid, acetic acid, formic acid, phosphoric acid, p-toluenesulfonic acid and its hydrate, methanesulfonic acid, trifluoromethanesulfonic acid, and cation exchange resins. Hydrochloric acid, methanesulfonic acid, and cation exchange resins are preferred, hydrochloric acid and cation exchange resins are more preferred, and hydrochloric acid is even more preferred. The amount of the acid used is usually preferably 0.001 to 1 mol, and more preferably 0.01 to 0.2 mol, per mol of the total number of moles of the trialkoxysilanes (6) and (7) and the optional alkoxysilanes (9) to (12).
[0048] The base is not particularly limited, and examples thereof include sodium hydroxide, potassium hydroxide, lithium hydroxide, sodium acetate, potassium acetate, lithium acetate, sodium carbonate, sodium hydrogencarbonate, sodium methoxide, sodium ethoxide, potassium methoxide, potassium ethoxide, potassium tert-butoxide, triethylamine, anion exchange resins, etc., with sodium hydroxide, potassium hydroxide, and sodium acetate being preferred, and sodium acetate being more preferred. The amount of the base used is usually preferably 0.001 to 1 mole, and more preferably 0.01 to 0.2 mole, per mole of the total number of moles of the trialkoxysilanes (6) and (7) and the optional alkoxysilanes (9) to (12).
[0049] The amount of water used in the copolymerization by hydrolysis and condensation is usually preferably 0.1 to 100 mol, more preferably 0.3 to 10 mol, and even more preferably 0.5 to 2.0 mol, per mol of the total number of moles of the trialkoxysilanes (6) and (7) and the optional alkoxysilanes (9) to (12). The reaction temperature for copolymerization by hydrolysis and dehydration condensation is not particularly limited, but is usually 20 to 150° C., preferably 30 to 120° C., more preferably 40 to 100° C., and even more preferably 50 to 80° C. The reaction time is usually 1 hour or more, and preferably 2 to 72 hours. The concentration temperature of the reaction mixture is not particularly limited, but is usually 10 to 150° C., and preferably 60 to 120° C. The pressure during concentration is not particularly limited, and may be either normal pressure or reduced pressure.
[0050] The stoichiometric ratio of the trialkoxysilanes (6) and (7) and the optional alkoxysilanes (9) to (12) is not particularly limited, but taking into consideration the fast curing property, hardness, and flex resistance of the resulting organopolysiloxane, it is preferable that the ratio be 0.001 to 1,000 moles of the alkoxysilane (7), 0 to 1,000 moles of the alkoxysilane (9), 0 to 1,000 moles of the alkoxysilane (10), 0 to 1,000 moles of the alkoxysilane (11), and 0 to 1,000 moles of the alkoxysilane (12) relative to 1 mole of the trialkoxysilane (6), more preferably. Relative to 1 mole of trialkoxysilane (6), the amounts are 0.01 to 100 moles of alkoxysilane (7), 0 to 100 moles of alkoxysilane (9), 0.001 to 100 moles of alkoxysilane (10), 0 to 100 moles of alkoxysilane (11), and 0 to 100 moles of alkoxysilane (12). More preferably, relative to 1 mole of trialkoxysilane (6), the amounts are 0.1 to 50 moles of alkoxysilane (7), 0 mole of alkoxysilane (9), 0.001 to 50 moles of alkoxysilane (10), 0 mole of alkoxysilane (11), and 0 mole of alkoxysilane (12).
[0051] Therefore, the organopolysiloxane of the present invention is preferably a vinyl group-containing organopolysiloxane obtained by copolymerizing trialkoxysilanes (6) and (7) with alkoxysilane (10) through hydrolysis and dehydration condensation. By using a compound obtained by reacting the trialkoxysilanes (6) and (7) with organohydrogenpolysiloxane (8) through subsequent hydrosilylation, even better fast curing properties, hardness, flexibility, hydrophobicity, and water sliding properties can be exhibited.
[0052] [ka] (In the formula, R 1 ~R 4 , n and m have the same meanings as above.)
[0053] The hydrosilylation of the vinyl group-containing organopolysiloxane and organohydrogenpolysiloxane (8) can be carried out in the presence of a platinum or rhodium catalyst in a solvent system or in a solventless system.
[0054] The reaction ratio of the vinyl group-containing organopolysiloxane and the organohydrogenpolysiloxane is preferably 0.1 to 2.0 Si-H groups of the organohydrogenpolysiloxane per vinyl group of the vinyl group-containing organopolysiloxane, more preferably 0.25 to 1.2 Si-H groups of the organohydrogenpolysiloxane. If the ratio is too low, excessive unreacted vinyl group-containing organopolysiloxane may remain, and if the ratio is too high, intermolecular crosslinking may proceed too far, resulting in unnecessary high molecular weight and reduced stability of the product.
[0055] The hydrosilylation catalyst may be a known catalyst such as platinum (Pt), a complex compound having Pt as a central metal, or a complex compound having rhodium as a central metal.Specific examples include an alcohol solution of chloroplatinic acid, a 1,3-divinyltetramethyldisiloxane complex of chloroplatinic acid, and a compound obtained by neutralizing the complex, a 1,3-divinyltetramethyldisiloxane complex having a central metal oxidation number of Pt(II) or Pt(0), and a rhodium Wilkinson catalyst.In terms of addition site selectivity, it is preferable that the complex has a central metal oxidation number other than Pt(IV), and in particular, a 1,3-divinyltetramethyldisiloxane complex having a central metal of Pt(0) or Pt(II) is preferable.
[0056] The amount of the hydrosilylation catalyst used is not particularly limited as long as it is an amount that exerts a catalytic effect in the hydrosilylation reaction, but is preferably 0.000001 to 1 mol %, more preferably 0.0001 to 0.01 mol %, relative to 1 mol of the vinyl group in (i). If it is less than 0.000001 mol %, a sufficient catalytic effect may not be exerted, whereas if it is more than 1 mol %, the effect may saturate, resulting in high production costs and uneconomical.
[0057] The temperature during the hydrosilylation reaction is preferably 50 to 150° C., more preferably 60 to 130° C., and even more preferably 70 to 110° C. If the temperature is less than 50° C., the reaction rate may be low and production efficiency may be poor. If the temperature exceeds 150° C., it becomes difficult to control the addition position, and addition isomers may be produced, as well as side reactions such as dehydrogenation reactions derived from the hydrosilyl group. The reaction time is preferably 30 minutes to 10 hours.
[0058] A solvent may be used when carrying out the hydrosilylation reaction. The solvent is not particularly limited as long as it does not inhibit the reaction or have reactivity with the raw materials, and examples thereof include alcohol-based solvents such as methanol, ethanol, and propanol; ether-based solvents such as diethyl ether, dimethoxyethane, and tetrahydrofuran; heteroelement-containing polar solvents such as acetonitrile and dimethylformamide; aliphatic hydrocarbon-based solvents such as hexane and heptane; and aromatic hydrocarbon-based solvents such as toluene and xylene. These solvents may be used alone or in combination of two or more.
[0059] The organopolysiloxane of the present invention has a kinetic viscosity at 25° C. of 10 to 10,000 mm 2 / s is preferable, and 30 to 5000 mm 2 / s is more preferable. 2 If the thickness is less than 10,000 mm / s, the desired hydrophobicity and water sliding properties may not be achieved. 2 If it is higher than 1 / s, the storage stability of the resulting polymer may be low and it may be difficult to handle. In the present invention, the kinematic viscosity is a value measured using a Cannon-Fenske viscometer according to the method described in JIS Z 8803:2011.
[0060] The curable composition and coating composition of the present invention (hereinafter, both will be referred to as the composition) contain at least the above-mentioned (A) organopolysiloxane and (B) curing catalyst. Since the composition of the present invention contains the above-mentioned organopolysiloxane of the present invention, when it is used to coat a solid substrate, the cured coating has improved fast curing properties, hardness, flexibility, hydrophobicity, and water sliding properties due to the structure of the organopolysiloxane of the present invention, compared to when conventional organopolysiloxanes are used.
[0061] The curing catalyst (B) is a component that accelerates the reaction in which the hydrolyzable silyl groups contained in the organopolysiloxane (A) undergo hydrolysis and condensation in the presence of moisture in the air, thereby accelerating the curing of the composition, and is added to achieve efficient curing. The amount of curing catalyst (B) added is not particularly limited, but in consideration of adjusting the curing rate within an appropriate range to produce a cured coating with the desired physical properties, improving workability during application, and further taking into account the economics associated with its addition, the amount is preferably 0.01 to 50 parts by mass, more preferably 0.05 to 10 parts by mass, and even more preferably 0.1 to 5 parts by mass, per 100 parts by mass of component (A).
[0062] The curing catalyst is not particularly limited as long as it is a curing catalyst used in the curing of a general moisture condensation curing composition, and specific examples thereof include alkyl tin compounds such as dibutyltin oxide and dioctyltin oxide; alkyl tin ester compounds such as dibutyltin diacetate, dibutyltin dilaurate, dioctyltin dilaurate, dibutyltin dioctoate, dioctyltin dioctoate, and dioctyltin diversatate; tetraisopropoxytitanium, tetra-n-butoxytitanium, tetrakis(2-ethylhexoxy)titanium, dipropoxybis( Titanium acetylacetonate, titanium diisopropoxybis(ethylacetoacetate), titanium isopropoxyoctylene glycol and other titanate esters, titanium chelate compounds and their partial hydrolysates; zinc naphthenate, zinc stearate, zinc 2-ethyloctoate, iron 2-ethylhexoate, cobalt 2-ethylhexoate, manganese 2-ethylhexoate, cobalt naphthenate, aluminum trihydroxide, aluminum alcoholates, aluminum acylates, salts of aluminum acylates, aluminum Aminosiloxy compounds, aluminum chelate compounds and other organometallic compounds; 3-aminopropyltrimethoxysilane, 3-aminopropyltriethoxysilane, 3-aminopropylmethyldimethoxysilane, 3-aminopropylmethyldiethoxysilane, N-β(aminoethyl)γ-aminopropyltrimethoxysilane, N-β(aminoethyl)γ-aminopropyltriethoxysilane, N-β(aminoethyl)γ-aminopropylmethyldimethoxysilane, N-β(aminoethyl)γ-aminopropylmethyldiethoxysilane, bis[3-(trimethoxy ... Aminoalkyl group-substituted alkoxysilanes such as N,N'-bis[3-(trimethoxysilyl)propyl]amine, bis[3-(triethoxysilyl)propyl]amine, N,N'-bis[3-(trimethoxysilyl)propyl]ethane-1,2-diamine, N,N'-bis[3-(triethoxysilyl)propyl]ethane-1,2-diamine, and N-phenyl-3-aminopropyltrimethoxysilane; amine compounds and salts thereof such as hexylamine, dodecylamine phosphate, and tetramethylguanidine; quaternary ammonium salts such as benzyltriethylammonium acetate;Examples of such silanes include lower fatty acid salts of alkali metals such as potassium acetate, sodium acetate, and lithium oxalate; dialkylhydroxylamines such as dimethylhydroxylamine and diethylhydroxylamine; silanes and siloxanes containing a guanidyl group such as tetramethylguanidylpropyltrimethoxysilane, tetramethylguanidylpropylmethyldimethoxysilane, tetramethylguanidylpropyltriethoxysilane, tetramethylguanidylpropylmethyldiethoxysilane, and tetramethylguanidylpropyltris(trimethylsiloxy)silane; and silanes and siloxanes containing a phosphazene base such as N,N,N',N',N'',N''-hexamethyl-N'''-[3-(trimethoxysilyl)propyl]-phosphorimidic triamide, which may be used alone or in combination of two or more kinds.
[0063] Among these, dioctyltin dilaurate, dioctyltin diversatate, tetraisopropoxytitanium, tetra-n-butoxytitanium, titanium diisopropoxybis(ethylacetoacetate), 3-aminopropyltrimethoxysilane, 3-aminopropyltriethoxysilane, N-β(aminoethyl)γ-aminopropyltrimethoxysilane, bis[3-(trimethoxysilyl)propyl]amine, N,N′-bis[3-(trimethoxysilyl)propyl]ethane-1,2-diamine, and tetramethylguanidylpropyltrimethoxysilane are preferred because of their excellent reactivity, and from the viewpoint of the curability of the composition, Of these, dioctyltin dilaurate, dioctyltin diversatate, tetra-n-butoxytitanium, 3-aminopropyltrimethoxysilane, 3-aminopropyltriethoxysilane, and tetramethylguanidylpropyltrimethoxysilane are more preferable, and tetra-n-butoxytitanium, 3-aminopropyltrimethoxysilane, 3-aminopropyltriethoxysilane, and tetramethylguanidylpropyltrimethoxysilane are even more preferable because they do not contain organic tin compounds and are less toxic, and tetra-n-butoxytitanium and 3-aminopropyltriethoxysilane are particularly preferable from the viewpoint of the curability of the composition.
[0064] Furthermore, for the purposes of adjusting the viscosity of the composition of the present invention to improve workability, or for the purposes of adjusting the curability of the composition and the hardness and flexibility of the resulting coating film, one or more compounds selected from silane compounds containing alkoxysilyl groups, silicone alkoxy oligomers having alkoxysilyl groups and / or silanol groups in one molecule, and silicone resins may be mixed in separately from the organopolysiloxane of component (A) depending on the intended use.
[0065] The silane compound containing an alkoxysilyl group is not particularly limited, but specific examples thereof include those exemplified as the above alkoxysilanes (9) to (12). The silicone alkoxy oligomer having an alkoxysilyl group and / or a silanol group in one molecule is not particularly limited, and may be commercially available.Specific examples thereof include X-40-9250, X-40-9246, X-40-9225, KR-500, KR-515, KC-89S, KR-401N, X-40-9227, KR-510, KR-9218, KR-400, X-40-2327, KR-401, etc., manufactured by Shin-Etsu Chemical Co., Ltd. The silicone resin is not particularly limited and may be a commercially available product, specific examples of which include KR-220L, KR-251, KR-112, KR-300, KR-311, KR-480, and KR-216 manufactured by Shin-Etsu Chemical Co., Ltd.
[0066] Furthermore, the composition of the present invention is preferably in a solvent-free form that does not substantially contain organic solvents (which are often harmful to the human body and flammable), but a solvent may be added depending on the application and workability. Here, the term "substantially" means that the solvent contained in the composition is 1% by mass or less, particularly 0.1% by mass or less. Specific examples of usable solvents include the same organic solvents as those used in the production of the organopolysiloxane (A). The solvent also includes those that are not intentionally added to the curable composition and the coating agent composition, such as reaction solvents that cannot be completely removed by distillation under reduced pressure.
[0067] Depending on the purpose of use, various additives such as adhesion improvers, inorganic and organic ultraviolet absorbers, light stabilizers, storage stability improvers, plasticizers, fillers, pigments, etc. may be added to the composition of the present invention.
[0068] The composition of the present invention described above is applied to the surface of a solid substrate and cured to form a coating layer, thereby obtaining a coated solid substrate that is a cured article. The coating method is not particularly limited, and specific examples thereof include spray coating, spin coating, dip coating, roller coating, brush coating, bar coating, flow coating, and other known methods that can be appropriately selected and used. The solid substrate is not particularly limited, and specific examples thereof include epoxy resins, phenolic resins, polycarbonates and polycarbonate blends, acrylic resins such as poly(methyl methacrylate), polyester resins such as poly(ethylene terephthalate), poly(butylene terephthalate), and unsaturated polyester resins, organic polymer substrates such as polyamide resins, polyimide resins, acrylonitrile-styrene copolymers, styrene-acrylonitrile-butadiene copolymers, polyvinyl chloride resins, polystyrene resins, blends of polystyrene and polyphenylene ether, cellulose acetate butyrate, and polyethylene resins, metal substrates such as steel plates, paint-coated surfaces, glass, ceramics, concrete, slate plates, textiles, wood, stone, roof tiles, inorganic fillers such as (hollow) silica, titania, zirconia, and alumina, and glass fiber products such as glass cloth, glass tape, glass mat, and glass paper, including glass fibers. The material and shape of the substrate are not particularly limited, but the composition of the present invention can be particularly suitably used for coating steel plates and glass.
[0069] When the composition of the present invention comes into contact with moisture in the atmosphere, the hydrolysis and condensation reaction of the organopolysiloxane (A) proceeds, and the curing reaction begins. As an indicator of the moisture in the atmosphere, any humidity of 10 to 100% RH may be used, and the moisture in the air is sufficient, but since the higher the humidity, the faster the hydrolysis proceeds, moisture may be added to the atmosphere as desired. The curing reaction temperature and time can be appropriately changed depending on factors such as the substrate used, water concentration, catalyst concentration, and type of hydrolyzable group, etc. Usually, it is about 1 minute to 1 week within the range not exceeding the heat resistance temperature of the substrate used. The composition of the present invention cures well even at room temperature, and therefore, even in cases where room temperature curing is essential, such as in on-site construction, the stickiness (tack) of the coating surface disappears within a few minutes to a few hours, providing excellent workability. However, heat treatment may be carried out within a temperature range that does not exceed the heat resistance of the substrate. EXAMPLES
[0070] The present invention will be specifically described below using examples and comparative examples, but the present invention is not limited to these.
[0071] In the following, the kinematic viscosity of each product is a value measured at 25°C using a Canon-Fenske viscometer according to the method described in JIS Z 8803:2011, and the molecular weight is a weight average molecular weight in terms of polystyrene determined by GPC measurement using a GPC (gel permeation chromatograph) device manufactured by Tosoh Corporation, toluene as a solvent, and RI as a detector. The average structure of the organopolysiloxane was measured using a 300 MHz NMR measurement device manufactured by JEOL Ltd. 1 H-NMR and 29 It was calculated from the integral value of the detected spectrum in Si-NMR. The content of silanol hydroxyl groups (mass %, hereinafter referred to as silanol amount) in each product was quantified from the amount of methane gas generated when each product was reacted with a Grignard reagent (methylmagnesium iodide). The content of vinyl groups in each product (mol / 100 g, hereafter referred to as vinyl value) was quantified by treating each product with Hanus solution, reacting it with an aqueous potassium iodide solution, and titrating the resulting iodine with sodium thiosulfate.
[0072] [1] Synthesis of organopolysiloxane [Synthesis Example 1] Synthesis of organopolysiloxane (1A) In a 5L separable flask equipped with a stirrer, reflux condenser, dropping funnel and thermometer, 1850g (13.6 mol) of methyltrimethoxysilane, 300g (1.8 mol) of methoxymethyltrimethoxysilane, 400g (2.7 mol) of vinylmethyldimethoxysilane and 0.7g of maleic anhydride were charged, and 347g of ion-exchanged water was dropped at 15°C under stirring, and hydrolysis and condensation were carried out at 70°C for 3 hours. Then, 60g of a strong acid cation exchange resin (Lewatit K2629 manufactured by LANXESS) was added, and hydrolysis and condensation were carried out for another 3 hours at 70°C. The reaction liquid obtained was distilled at normal pressure, and after the distillate ceased to come out, the condensation reaction was promoted at 105°C for 3 hours. Finally, the distillate was removed by reduced pressure distillation (90°C, 1.3 kPa) to obtain organopolysiloxane (1A) (yield 1410g). The obtained organopolysiloxane 1A was a colorless, transparent liquid represented by the following average structural formula and had a kinetic viscosity of 62 mm 2 The molecular weight was 2,700, the content of silanol hydroxyl groups was 0.3 mass%, and the vinyl value was 0.15 mol / 100 g.
[0073] [ka]
[0074] [Production Example 1-1] Synthesis of organopolysiloxane (1B) In a 1L separable flask equipped with a stirrer, reflux condenser, dropping funnel and thermometer, 200 g of the organopolysiloxane (1A) obtained in Synthesis Example 1, 95 g of the following hydrogensiloxane (8-1) (reaction molar ratio, vinyl group:Si-H group = 4:1), and 180 g of toluene were charged, and 0.0004 moles of 1,3-divinyltetramethyldisiloxane complex of Pt(0) per mole of Si-H group was added at 80°C under stirring, and hydrosilylation was carried out at 80°C for 3 hours. The fraction was then removed by vacuum distillation (90°C, 1.3 kPa), and organopolysiloxane (1B) was obtained (yield 282 g). The obtained organopolysiloxane (1B) was a colorless and transparent liquid represented by the following average structural formula, and had a kinetic viscosity of 635 mm 2 / s, Mw 26,400, and the content of silanol hydroxyl groups was 0.1 mass%.
[0075] [ka]
[0076] [ka]
[0077] [Production Example 1-2] Synthesis of organopolysiloxane (1C) In a 1L separable flask equipped with a stirrer, reflux condenser, dropping funnel and thermometer, 200 g of the organopolysiloxane (1A) obtained in Synthesis Example 1, 45 g of the following hydrogensiloxane (8-2) (reaction molar ratio, vinyl group:Si-H group=4:1), and 180 g of toluene were charged, and 0.0004 moles of 1,3-divinyltetramethyldisiloxane complex of Pt(0) was added per mole of Si-H group at 80°C under stirring, and hydrosilylation was carried out at 80°C for 3 hours. The fraction was then removed by vacuum distillation (90°C, 1.3 kPa), and organopolysiloxane (1C) was obtained (yield 240 g). The obtained organopolysiloxane (1C) was a colorless, transparent liquid represented by the following average structural formula, and had a kinetic viscosity of 341 mm 2 / s, Mw 17,800, and the content of silanol hydroxyl groups was 0.1 mass%.
[0078] [ka]
[0079] [ka]
[0080] [Production Example 1-3] Synthesis of organopolysiloxane (1D) In a 1L separable flask equipped with a stirrer, reflux condenser, dropping funnel and thermometer, 200 g of the organopolysiloxane (1A) obtained in Synthesis Example 1, 123 g of the following hydrogensiloxane (8-3) (reaction molar ratio, vinyl group:Si-H group=4:1), and 180 g of toluene were charged, and 0.0004 moles of 1,3-divinyltetramethyldisiloxane complex of Pt(0) was added per mole of Si-H group at 80°C under stirring, and hydrosilylation was carried out at 80°C for 3 hours. The fraction was then removed by distillation under reduced pressure (90°C, 1.3 kPa), and organopolysiloxane (1D) was obtained (yield 313 g). The obtained organopolysiloxane (1D) was a colorless, transparent liquid represented by the following average structural formula, and had a kinetic viscosity of 1329 mm 2 / s, Mw 34,300, and the content of silanol hydroxyl groups was 0.1 mass%.
[0081] [ka]
[0082] [ka]
[0083] [Production Example 1-4] Synthesis of organopolysiloxane (1E) In a 1L separable flask equipped with a stirrer, reflux condenser, dropping funnel and thermometer, 200 g of the organopolysiloxane (1A) obtained in Synthesis Example 1, 193 g of the following hydrogensiloxane (8-4) (reaction molar ratio, vinyl group:Si-H group=4:1), and 180 g of toluene were charged, and 0.0004 moles of 1,3-divinyltetramethyldisiloxane complex of Pt(0) per mole of Si-H group was added at 80°C under stirring, and hydrosilylation was carried out at 80°C for 3 hours. The fraction was then removed by vacuum distillation (90°C, 1.3 kPa), and organopolysiloxane (1E) was obtained (yield 385 g). The obtained organopolysiloxane (1E) was a colorless, transparent liquid represented by the following average structural formula, and had a kinetic viscosity of 4714 mm 2 / s, Mw 70,000, and the content of silanol hydroxyl groups was 0.1 mass%.
[0084] [ka]
[0085] [ka]
[0086] [Synthesis Example 2] Synthesis of organopolysiloxane (2A) In a 1L separable flask equipped with a stirrer, reflux condenser, dropping funnel and thermometer, 370g (3.08 mol) of methyltrimethoxysilane, 80g (0.54 mol) of vinylmethyldimethoxysilane and 0.14g of maleic anhydride were charged, and 69.4g of ion-exchanged water was dropped at 15°C under stirring, and hydrolysis and condensation were carried out at 70°C for 3 hours. Then, 12g of a strong acid cation exchange resin (Lewatit K2629 manufactured by LANXESS) was added, and hydrolysis and condensation were carried out for another 3 hours at 70°C. The reaction liquid obtained was distilled at normal pressure, and after the distillate ceased to come out, the condensation reaction was promoted at 105°C for 3 hours. Finally, the distillate was removed by reduced pressure distillation (90°C, 1.3kPa), and organopolysiloxane (2A) was obtained (yield 290g). The obtained organopolysiloxane (2A) was a colorless, transparent liquid represented by the following average structural formula and had a kinetic viscosity of 66 mm 2The copolymer had a molecular weight of 3100, a silanol hydroxyl group content of 0 mass%, and a vinyl value of 0.15 mol / 100 g.
[0087] [ka]
[0088] [Comparative Example 1-1] Synthesis of organopolysiloxane (2B) In a 1L separable flask equipped with a stirrer, reflux condenser, dropping funnel and thermometer, 200g of the organopolysiloxane (2A) obtained in Synthesis Example 2, 95g of the above hydrogensiloxane (8-1) (reaction molar ratio, vinyl group:Si-H group=4:1), and 180g of toluene were charged, and 0.0004 moles of 1,3-divinyltetramethyldisiloxane complex of Pt(0) was added per mole of Si-H group at 80°C under stirring, and hydrosilylation was carried out at 80°C for 3 hours. The fraction was then removed by vacuum distillation (90°C, 1.3kPa), and organopolysiloxane (2B) was obtained (yield 290g). The obtained organopolysiloxane (2B) was a colorless, transparent liquid represented by the following average structural formula, and had a kinetic viscosity of 191mm. 2 / s, Mw 13,000, and the content of silanol hydroxyl groups was 0 mass%.
[0089] [ka]
[0090] [2] Coating composition [Examples 2-1 to 2-6, Comparative Examples 2-1 to 2-3, Reference Example 2-1] The organopolysiloxanes and curing catalysts obtained in the above Production Examples 1-1 to 1-4, Comparative Example 1-1, and Synthesis Example 1 were mixed in the amounts shown in Table 1 to prepare the coating compositions of Examples 2-1 to 2-6, Comparative Examples 2-1 to 2-3, and Reference Example 2-1.
[0091] [Table 1] KR-400: Methyl silicone coating agent (Shin-Etsu Chemical Co., Ltd.) TBT: Tetrabutyl titanate KBE-903: 3-Aminopropyltriethoxysilane MGPM: Tetramethylguanidylpropyltrimethoxysilane
[0092] Each of the coating compositions obtained above was applied to a glass plate or a polished steel plate using a bar coater No. 14 under air at 25°C and 50% RH, and then dried and cured for one day under air at 25°C and 50% RH to produce a cured film. The obtained cured films were evaluated as follows. The results are shown in Table 2. [Dry time to touch] The coating composition was applied to a glass plate by the above coating method, and the obtained test piece was left in an air atmosphere of 25°C and 50% RH. The time until the coating film no longer adhered to the finger when pressed against the coated surface due to the progress of moisture curing was recorded. The smaller the value, the better the curability. [Pencil hardness] The test pieces having the cured coating formed on the glass plate by the above coating method were subjected to measurement with a load of 750 g according to the pencil scratch test method described in JIS K 5600-5-4, and the results are shown below. [Bending resistance] Test pieces in which a hardened coating was formed on polished steel sheets using the above coating method were measured using a cylindrical mandrel (Type 1) in accordance with the method described in JIS K 5600-5-1, and the results are shown below. [Water repellency / sliding property] A drop (about 2 μl) of purified water was dropped onto a test piece in which a hardened coating was formed on a polished steel plate by the above coating method, and the contact angle of water was measured using a contact angle meter (instrument name: Drop Master DM-701, manufactured by Kyowa Interface Science Co., Ltd.) to evaluate water repellency. A contact angle desirable for water repellency is generally a value of 100° or more. In addition, a drop (about 20 μl) of purified water was dropped onto the same test piece, and the test piece was gradually tilted from a horizontal position, and the angle at which the water droplet began to flow was taken as the water sliding angle to evaluate water slippage (water sliding property). The evaluation criteria were as follows: a water sliding angle of less than 35° was marked as ○, a water sliding angle in the range of 35 to 45° was marked as △, and a water sliding angle of more than 45° was marked as ×.
[0093] [Table 2]
[0094] [Examples 3-1 to 3-6, Comparative Examples 3-1 to 3-3, Reference Example 3-1] The organopolysiloxanes and curing catalysts obtained in the above Production Examples 1-1 to 1-4, Comparative Example 1-1, and Synthesis Example 1 were mixed in the amounts shown in Table 3 to prepare the coating agent compositions of Examples 3-1 to 3-6, Comparative Examples 3-1 to 3-3, and Reference Example 3-1.
[0095] [Table 3] KR-400: Methyl silicone coating agent (Shin-Etsu Chemical Co., Ltd.) TBT: Tetrabutyl titanate MGPM: Tetramethylguanidylpropyltrimethoxysilane DX9740: Aluminum alkoxide compound (Shin-Etsu Chemical Co., Ltd.) Isopar G: Isoparaffin-based organic solvent (initial boiling point 166°C, dry point 177°C, manufactured by ExxonMobil)
[0096] The following evaluations were carried out using each of the coating compositions obtained above. The results are shown in Table 4. [Workability] 2 ml of each of the above coating compositions was dropped onto a black-coated plate (material: SPCC-SD, standard: JIS-G-3141, dimensions: 0.8 mm x 70 mm x 150 mm, one side of which was coated with black amino alkyd paint after chemical electrodeposition, manufactured by Asahi B-Techno Co., Ltd.), thinly applied by hand using tissue paper, and left to stand at 25°C for 5 minutes. The excess was then wiped off with a dry microfiber cloth. At this time, those that could be wiped off easily and evenly were rated as ○, those that had slight unevenness or were somewhat difficult to wipe off were rated as △, and those that had significant unevenness or were difficult to wipe off and were difficult to apply were rated as ×. [Curability] A test piece was prepared by applying the coating composition in the same manner as in the workability evaluation. This was then left to stand for 2 hours at 25°C to cure and obtain a test piece with a cured film. When the coating surface of the obtained test piece was touched with a finger, those that had no tack remaining and exhibited slipperiness were rated as ◯, those that had no tack remaining but did not exhibit slipperiness were rated as △, and those that had tack remaining were rated as ×. [Water repellency / sliding property] A test piece was prepared by applying the coating composition in the same manner as in the workability evaluation. This was further left to stand at 25°C for 2 hours to cure and harden, and a test piece with a hardened film was obtained. A drop of purified water (about 2 μl) was dropped onto the obtained test piece, and the contact angle of water was measured using a contact angle meter (device name: Drop Master DM-701, manufactured by Kyowa Interface Science Co., Ltd.) to evaluate water repellency. A contact angle desirable for water repellency is generally a value of 100° or more. In addition, a drop of purified water (about 20 μl) was dropped onto the same test piece, and the test piece was gradually tilted from a horizontal state, and the angle at which the water droplet began to flow was used as the water sliding angle to evaluate water sliding (water sliding property). The evaluation criteria were as follows: a water sliding angle of less than 35° was marked as ○, a water sliding angle in the range of 35 to 45° was marked as △, and a water sliding angle of more than 45° was marked as ×. [Wear resistance] A test piece was prepared by applying the coating composition in the same manner as in the workability evaluation. This was further left to stand at 25°C for 12 hours to cure and harden, and a test piece with a cured film was obtained. A wear resistance test was performed on the surface of the obtained test piece on which the cured film was prepared, using a simple friction tester (manufactured by Imoto Manufacturing Co., Ltd.). Specifically, a moving plate to which the test piece was fixed moved at a speed of 30 times per minute with a distance of 100 mm per round trip, and a friction object with a load of 500 g applied by a weight was placed in the center and moved back and forth 400 times to perform wear. The water contact angle of the surface after wear was measured in the same manner as the water repellency and water sliding test, and wear resistance was evaluated. The wear resistance was evaluated as follows: if the water contact angle after 400 round trips was more than 90% of the water contact angle before wear, it was marked as ○; if it was in the range of 75 to 90%, it was marked as △; if it was less than 75%, it was marked as ×. The friction material used in the test was a 40 mm wide dry and clean cloth (absorbent cloth made of cellulose / cotton composite fiber, ThreeBond product "ThreeBond 6644E") soaked in distilled water and wrapped around a 20 mm diameter stainless steel cylinder, and was placed so that the axis of the cylinder was oriented perpendicular to the moving direction of the moving plate.
[0097] [Table 4]
[0098] As shown in Tables 2 and 4, the coating agents using the organopolysiloxanes obtained in Production Examples 1-1 to 1-4 have excellent fast curing properties even when an amine compound is used as a curing catalyst, and the obtained cured films have both hardness and flex resistance, as well as excellent water repellency and water sliding properties. On the other hand, it is understood that coating agents using organopolysiloxanes that do not have the structural unit represented by general formula (1) have a long dry time to touch and are poor in rapid curing properties, and the resulting cured films have poor abrasion resistance. It is also clear that films obtained from coating agents using organopolysiloxanes that do not have the structural unit represented by the above general formula (2) are inferior in water repellency, water slip, workability, and abrasion resistance.
Claims
1. A method for producing a cured product, comprising curing a curable composition containing (A) an organopolysiloxane having a structural unit represented by the following general formula (1), a structural unit represented by the following general formula (2), and a group represented by the following general formula (3), which is directly bonded to a silicon atom, and (B) a curing catalyst: 【Chemistry 1】 (In the formula, R 1 represents an unsubstituted or substituted alkyl group having 1 to 12 carbon atoms, or an unsubstituted or substituted aryl group having 6 to 10 carbon atoms. 【Chemistry 2】 (In the formula, R 2 each independently represents an unsubstituted or substituted alkyl group having 1 to 12 carbon atoms, or an unsubstituted or substituted aryl group having 6 to 10 carbon atoms, each n independently represents 2 or 3, and m represents an integer from 5 to 100. 【Chemistry 3】 (In the formula, R 3 represents a hydrogen atom, an unsubstituted or substituted alkyl group having 1 to 10 carbon atoms, or an unsubstituted or substituted aryl group having 6 to 10 carbon atoms.
2. The method for producing a cured product according to claim 1, wherein the curable composition is applied to the surface of a solid substrate and then cured.
3. The method for producing a cured product according to claim 1 or 2, wherein the average structure of the organopolysiloxane is represented by the following formula (4): 【Chemistry 4】 (In the formula, R 1 , R 2 , R 3 , n and m have the same meanings as above, R 4 , R 5 and R 6 Each independently represents a monovalent organic group, and a, b, c, d, e, f, and g represent the numbers a>0, b>0, c>0, d>0, e>0, f>0, and g>0.
4. The method for producing a cured product according to claim 3, wherein the average structure of the organopolysiloxane is represented by the following formula (5): 【Chemistry 5】 (In the formula, R 1 , R 2 , R 3 , R 4 , n, m, a, b, and g have the same meanings as above, and d represents a number d>0.
5. The method for producing a cured product according to any one of claims 1 to 4, wherein the curing catalyst (B) is an amine compound.
Citation Information
Patent Citations
Alkoxy-crosslinkable one-component moisture-curing materials
JP2004536957A
Composition for use in membrane formation, forming method for membrane, and silica-based membrane
JP2005179587A
Curable composition
JP2014114434A
Organopolysiloxane and coating composition containing the same
JP2021080307A
Room-temperature-curable resin composition, coating material, adhesive, sealing material, and article
WO2020189463A1